Serum biomarkers of iron stores are associated with worse physical health-related quality of life in nondialysis-dependent chronic kidney disease patients with or without anemia. Issue 9 (24th February 2021) - Guedes, Murilo; Muenz, Daniel; Zee, Jarcy; Lopes, Marcelo Barreto; Waechter, Sandra; Stengel, Bénédicte; Massy, Ziad A; Speyer, Elodie; Ayav, Carole; Finkelstein, Fredric; Sesso, Ricardo; Pisoni, Ronald L; et al.
Abstract: Background: Iron deficiency (ID) is a common condition in nondialysis-dependent chronic kidney disease (NDD-CKD) patients that is associated with poorer clinical outcomes. However, the effect of ID on health-related quality of life (HRQoL) in this population is unknown. We analyzed data from a multinational cohort of NDD-CKD Stages 3–5 patients to test the association between transferrin saturation (TSAT) index and ferritin with HRQoL. Methods: Patients from Brazil ( n  = 205), France ( n  = 2015) and the USA ( n  = 293) in the Chronic Kidney Disease Outcomes and Practice Patterns Study (CKDopps, 2013–2019) were included. We evaluated the association of TSAT and ferritin (and functional and absolute ID, defined as TSAT ≤20% and ferritin ≥300 or <50 ng/mL) on pre-specified HRQoL measures, including the 36-item Kidney Disease Quality of Life physical component summary (PCS) and mental component summary (MCS) as the primary outcomes. Models were adjusted for confounders including hemoglobin (Hb). Results: TSAT ≤15% and ferritin <50 ng/mL and ≥300 ng/mL were associated with worse PCS scores, but not with MCS. Patients with composite TSAT ≤20% and ferritin <50 or ≥300 ng/mL had lower functional status and worse PCS scores than those with a TSAT of 20–30% and ferritin 50–299 ng/mL. Patients with a lower TSAT were less likely to perform intense physical activity. Adjustment for Hb only slightly attenuated the observed effects. Conclusions: Low TSAT levels, as well as both low TSAT with low ferritin and low TSAT with high ferritin, are associated with worse physical HRQoL in NDD-CKD patients, even after accounting for Hb level. Interventional studies of iron therapy on HRQoL among NDD-CKD individuals are needed to confirm these findings.